Modulation of laser-evoked potentials and pain perception by transcutaneous electrical nerve stimulation (TENS): A placebo-controlled study in healthy volunteers - Vassal, François; Créac’h, C.; Convers, Ph; Laurent, B.; Garcia-Larrea, L.; Peyron, R. (Clinical neurophysiology, 2013)
•High-frequency TENS causes inhibition of LEPs and evoked pain perception.•This modulation reflects an objective inhibitory effect of TENS on pain pathways.•This modulation predominates within the segmental area of TENS application. To investigate the effects of transcutaneous electrical nerve stimulation (TENS) on brain nociceptive responses (laser-evoked potentials, LEPs) and pain perception. Twenty healthy subjects were included. Nociceptive CO2-laser pulses were sequentially delivered to the dorsum of both feet. The amplitude of LEPs and nociceptive thresholds were collected in three consecutive conditions: T1: “sham” TENS (2Hz/low-intensity) positioned heterotopically, over the left thigh; T2: “active” TENS (120Hz/low-intensity) applied homotopically, over the left common peroneal nerve; and T3: “sham” TENS (replication of condition T1). Compared with “sham” TENS, “active” TENS significantly decreased the LEPs amplitude. This effect was observed exclusively when “active” TENS was applied ipsilaterally to the painful stimulus. Nociceptive thresholds increased with sessions in both limbs, but the increase observed during the “active” condition of TENS (T2) exceeded significantly that observed during the condition T3 only on the foot ipsilateral to TENS. Compared with a credible placebo TENS, high-frequency TENS induced a significant attenuation of both the acute pain and LEPs induced by noxious stimuli applied on the same dermatome. This modulation of subjective and objective concomitants of pain processing reflects a real neurophysiological TENS-related effect on nociceptive transmission.